Inflation Targeting in Practice : Strategic and Operational Issues and Application to Emerging Market Economies. (Washington, D.C. : International Monetary Fund, 2000)
A growing number of countries are anchoring their monetary policy through explicit inflation targeting. This policy has already scored remarkable successes in several countries, establishing central bank credibility, and reining in inflation where it had long been stubbornly high. But implementing inflation targets raises many difficult questions. What prerequisites must an economy and its institutions meet for the strategy to work? What choices should central banks make from the menu of possible variations on the basic approach? This book summarizes the discussions in a seminar at which economists and policymakers from ten countries reviewed their experiences with inflation targeting.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet